Design and synthesis of peptides from bacterial ParE toxin as inhibitors of topoisomerases - Bertucci Barbosa, Luiz Carlos [UNESP]; Garrido, Saulo Santesso [UNESP]; Garcia, Anderson [UNESP]; Delfino, Davi Barbosa [UNESP]; Santos, Laura do Nascimento [UNESP]; Marchetto, Reinaldo [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2012)
Toxin-antitoxin (TA) proteic systems encode a toxin and an antitoxin that regulate the growth and death of bacterial cells under various stress conditions. The ParE protein is a toxin that inhibits DNA gyrase activity and thereby blocks DNA replication. Based on the Escherichia coli ParE structure, a series of linear peptides were designed and synthesized by solid-phase methodology. The ability of the peptides to inhibit the activity of bacterial topoisomerases was investigated. Four peptides (ParELC3, ParELC8, ParELC10 and ParELC12), showed complete inhibition of DNA gyrase supercoiling activity with an IC100 between 20 and 40 mu mol L-1. In contrast to wild-type ParE, the peptide analogues were able to inhibit the DNA relaxation of topoisomerase IV, another type IIA bacterial topoisomerase, with lower IC100 values. Interestingly only ParELC12 displayed inhibition of the relaxation activity of human topoisomerase II. Our findings reveal new inhibitors of bacterial topoisomerases and are a good starting point for the development of a new class of antibacterial agents that targets the DNA topoisomerases. (C) 2012 Elsevier Masson SAS. All rights reserved.
Keywords: Peptides; TA systems; ParE toxin; DNA topoisomerases; Enzyme inhibition